Analysis of Friday Sermon Duration: Intellectual Reflection of Classical and Contemporary Islamic Scholars. (6th April 2022) - Usman, Abur Hamdi; Iskandar, Azwar
Abstract: Long Friday sermons in Malaysia have existed and functioned every week with no changes in terms of the quality of the sermon presentation. Indeed, the assessment of the quality of Friday sermon (khuṭbah) delivery is often linked to the process of preaching over the pulpit. Many stakeholders still question the quality of sermons because Muslims must listen to them as part of fulfilling the requirement of attending Friday's prayer. Furthermore, some of the congregation falls asleep during Friday sermons due to the influence of the times like hectic work schedule, and a less pleasant atmosphere in the mosque. Given this situation, the current article analyses the Hadiths that discuss the delivery duration of the Friday sermon. Based on a content analysis of sermons, this study finds that both classical and modern scholars agree that shortening the sermon is a sign of one's expertise in religious affairs. This is because the congregation tends to be less focused on receiving a sermon if the delivery is too long. Furthermore, the attractiveness and presentation of the Preacher (Khaṭīb) are based solely on solemn sermon texts, while the issues conveyed do not follow current developments.